2017
DOI: 10.1007/s40273-017-0527-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Pembrolizumab vs. Standard-of-Care Chemotherapy as First-Line Treatment for Metastatic NSCLC that Expresses High Levels of PD-L1 in the United States

Abstract: ObjectivesOur objectives were to evaluate the cost effectiveness of pembrolizumab compared with standard-of-care (SoC) platinum-based chemotherapy as first-line treatment in patients with metastatic non-small-cell lung cancer (NSCLC) that expresses high levels of programmed death ligand-1 (PD-L1) [tumour proportion score (TPS) ≥50%], from a US third-party public healthcare payer perspective.MethodsWe conducted a partitioned-survival model with a cycle length of 1 week and a base-case time horizon of 20 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
131
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(134 citation statements)
references
References 27 publications
3
131
0
Order By: Relevance
“…This result may guide the therapeutic decision between a pembrolizumab-chemotherapy combination and monotherapy although the fact remains that there is no data about this comparison. Finally, health-related quality-of-life is improved with pembrolizumab than with chemotherapy 26 and is more cost-effective, 27,28 but there are no health-related QOL data for pembrolizumab-chemotherapy even if the combination would appears to be cost-effective. 29 The results of this retrospective observational study should be considered in the context of the strengths and limitations of the data source and study design.…”
Section: Discussionmentioning
confidence: 99%
“…This result may guide the therapeutic decision between a pembrolizumab-chemotherapy combination and monotherapy although the fact remains that there is no data about this comparison. Finally, health-related quality-of-life is improved with pembrolizumab than with chemotherapy 26 and is more cost-effective, 27,28 but there are no health-related QOL data for pembrolizumab-chemotherapy even if the combination would appears to be cost-effective. 29 The results of this retrospective observational study should be considered in the context of the strengths and limitations of the data source and study design.…”
Section: Discussionmentioning
confidence: 99%
“…The Second Panel on Cost-Effectiveness in Health and Medicine recommended the inclusion of both the societal perspective and health system perspective for the sake of consistency and comparability of cost-effectiveness analyses 29 ; however, because of the lack of consistency in the conceptualization and interpretation of the societal perspective, to our knowledge it is unclear whether the comparability of cost-effectiveness analyses estimates will be improved by promoting a societal perspective. 18,32 A study by Insinga et al conducted in the United States demonstrated that pembrolizumab plus chemotherapy was cost-effective, with an ICER of $104,823 per QALY compared with chemotherapy. The majority of US-based cost-effectiveness analyses aim to support the payer's decision making regarding the coverage and reimbursement of health care.…”
Section: Discussionmentioning
confidence: 99%
“…Two US-based studies demonstrated that pembrolizumab monotherapy was cost-effective compared with platinum-based chemotherapy. 18,32 A study by Insinga et al conducted in the United States demonstrated that pembrolizumab plus chemotherapy was cost-effective, with an ICER of $104,823 per QALY compared with chemotherapy. 33 The authors found that the addition of pembrolizumab to chemotherapy extended life expectancy by 2.04 years compared with chemotherapy (3.96 years vs 1.92 years), which to our knowledge has not been observed previously among treatment-naive patients with metastatic, nonsquamous NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with PD and receiving salvage chemotherapy and supportive care, the estimated cost was derived from a published study . An end‐of‐life care cost of $32,841 was applied to each death . The costs of T790 M mutation screening ($966) and tissue biopsy ($3,548) were included in the second‐line osimertinib strategy .…”
Section: Methodsmentioning
confidence: 99%